(untitled) (Research, Society and Development, 2023)
Health care for women in different stages of life, regardless of social, economic, cultural and affective conditions, is essential. Pregnancy is a time of great transformation for women, extending to all family members. In this way, the present research sought to know the reality of the pregnant women assisted in the Alô Bebê Program, installed at the Hospital Materno Infantil in the municipality of Pinheiro-MA. In addition, it was intended to understand the relationship between the service offered and the quality of high-risk pregnancies, as well as the evaluation of the social worker responsible for the care of pregnant women. For the elaboration of the research, a bibliographic survey was used, interviews with the pregnant women and the social worker through a semi-structured questionnaire with a qualitative research route. Thus, it was verified that women are being increasingly encouraged to carry out prenatal consultations and to take care of themselves through high-risk pregnancies. In this research, we will highlight the responses of 17 pregnant women and a social worker who works closely to support pregnant women and adolescents. From these responses, several reflections emerged, making it possible to have a broad discussion on the importance of monitoring high-risk pregnancies. Finally, it is concluded that in fact a multidisciplinary team, reception, assistance from the social worker, and the support of the Unified Health System with the Alô Baby Program are fundamental for the pregnant women assisted to feel safe at that moment.